JavaScript quan wei zhi nan (yuan shu di qi ban) = JavaScript : the definitive guide : seventh edition / = JavaScript : the definitive guide - Flanagan, David (O' Reilly jing pin tu shu xi lie, 2021)
Detailed summary in vernacular field.